Ectopic Infra Orbital Nerves: Case Series of a Dangerous Normal Variant - Sandeep Jakhere; Veena Kalmath; Uma Chillalshetti (Acta Medica Indonesiana)
Normal variations in the paranasal sinus region are well documented in literature. We present five cases of a little known normal variant, which can have serious implications for the patient as well as the operating surgeon. An ectopic infra orbital nerve canal coursing through the maxillary sinus has rarely been described in imaging literature. This may sometimes be mistaken for a simple septum in the maxillary sinus and may cause serious complications during Functional Endoscopic sinus surgery (FESS) surgeries. We describe the imaging findings and present a brief review of the previous publications on the same subject.